Who owns Caribbean mass media? Foreign domination - a passing phase. - Lent, John A. (1991)
Notes that while the peak of foreign domination of Caribbean mass media has passed, foreign owners have not vanished totally. A phenomenon of recent years has been the development and strengthening of media groups and conglomerates with media properties, primarily owned within the region, but often connected to multinational corporations and local politics. Points out that there are no easy answers as to who should own the Caribbean mass media.